Human Resource Flexibility and its role in Job Maturity: An analytical study of the opinions of a sample of employees in private hospitals in Sulaymaniyah Governorate - Muhssen Jalal, Lanja (Iraqi Journal for Administrative Sciences, 2025)
This research aims to identify the role of human resources flexibility in achieving job maturity in a number of private hospitals in Sulaymaniyah Governorate, which numbered (8) hospitals. After reviewing the relevant literature and previous studies, the theoretical framework was developed, along with the construction of the conceptual model and research hypotheses based on the concepts of human resource flexibility and job maturity. Based on the nature and objectives of the study, the descriptive-analytical approach was adopted, and a questionnaire was used as the main tool for collecting field data. A total of (100) questionnaires were distributed among employees working in private hospitals in Sulaymaniyah Governorate, of which (81) were returned, and (61) were deemed valid for statistical analysis. To analyze the data, several statistical methods were employed, including Cronbach’s Alpha to verify reliability and validity, factor analysis, simple correlation, and structural equation modeling, using)SPSS-24( and )AMOS-24( software. The results revealed a significant correlation and impact relationship between the independent and dependent variables. Based on these findings, several recommendations were proposed, most notably the need to enhance employees’ decision-making abilities, encourage a culture of teamwork and responsibility, and provide a motivating work environment that supports critical thinking and learning from mistakes, all of which contribute to strengthening employees’ job maturity